Literatur Review: Peran Budaya Dalam Mempengaruhi Komunikasi Pasien Dengan Perawat: Tantangan Dan Peluang - Syarli, Setiadi; Arini, Larasuci (Barongko: Jurnal Ilmu Kesehatan, 2025)
Communication between patients and nurses is a crucial element in providing effective healthcare services. However, this communication is often influenced by various cultural factors that can create both challenges and opportunities. This study aims to explore the role of culture in communication between patients and nurses, highlighting the challenges faced and the opportunities that can be leveraged to enhance this interaction. Through an in-depth literature review, it was found that a better understanding of patients' cultural values can improve satisfaction, adherence to treatment, and overall health outcomes.